Online learning and learner autonomy: a comparative study of Turkish and Indonesian EFL students’ perspectives - Derinalp, Pelin; Karjo, Clara Herlina; Andreani, Wiwik; Ying, Yi; Herawati, Agnes (Journal of Education and Learning (EduLearn), 2025)
Advancements in technology has affected almost all aspects of life all around the world. The education sector is not an exception. As in many other countries, in Turkey and Indonesia, learning activities have been switched from face-to-face to online mode for several reasons such as the COVID-19 pandemic or the destructive earthquake in Turkey. Online learning has brought some challenges with it. As online learning requires learner autonomy, it is crucial to investigate learners´ perspectives regarding how this shift from traditional face-to-face teaching to online mode has affected the learners. Hence, the current study aims to investigate and compare Turkish and Indonesian English as a foreign language (EFL) students’ learner autonomy level. A quantitative study has been conducted among undergraduate students from Turkey (100) and Indonesia (120). Data was collected through a 30-item questionnaire and distributed online. The analysis was done quantitatively using descriptive statistical computation. The results show that both Indonesian and Turkish EFL students have high learner autonomy levels. However, some differences were identified in terms of their planning of learning ability (PLA), monitoring of learning, and evaluation of learning abilities. In light of this study’s findings, educational institutions are encouraged to promote strategies to assist students to be autonomous learners.